Analisa Laju Perpindahan Kalor Pada Alat Penukar Panas Kondensor Pembangkit Listrik Tenaga Uap (PLTU) di. PT XYZ - Yanto; Erwin Pardede (CV MEDAN TEKNO SOLUSI, 2023)
A heat exchanger is a device used to transfer heat between two or more fluids that have different temperatures, namely a fluid with a high temperature to a fluid with a low temperature. The heat transfer is either directly or indirectly. The components contained in the heat exchanger are shell, tube, buffle. The exchange rate of heat transfer in the heat exchanger is co-current and counter-flow. The effect of the fluid flow rate on the heat transfer rate aims to determine the effect of the fluid flow rate on the heat transfer that will be obtained when the heat exchanger cools. The heat exchanger used is a shell and tube heat exchanger. Based on the results of observations and discussion, it is obtained that the value of the heat transfer rate with a different flow rate will affect the heat transfer rate obtained. from the calculation of the overall heat transfer rate with a cooling fluid flow rate of 587.1501 Kg/s of 9707788.01 Kcal/s, 588.4101 Kg/s of 9791147.36 Kcal/s and a flow rate of 589.6701 Kg/s of 10374809, 06 Kcal/s. From the graph it can be seen that the greater the flow rate of the cooling fluid, the greater the rate of heat transfer that occurs.